Contextualizing and Scaling up Science Information Literacy in Introductory Biology Laboratories. Issue 2 (3rd April 2017) - Fuselier, Linda; Detmering, Robert; Porter, Toccara
ABSTRACT: Contributing to ongoing research on the pedagogy of science information literacy, this article describes the contextualization of instruction within a consequential, biology-related public health issue and assesses the impact of this approach on student learning across a large number of course sections. Contextualized science information literacy lessons were presented in an introductory, general education biology lab. Lessons were assessed through a comparison of information literacy skills of students enrolled in the lab and lecture versus those enrolled in the lecture only. Results indicated that students in the lab had greater perceived confidence in their information skills and improved information-seeking methods, relative to lecture-only students who did not receive the contextualized information literacy content.